Educação ambiental na Amazônia: uma experiência interdisciplinar - Ribeiro, Cilene Maria Melado Alvim (2020)
This research provided, through an extension project, interdisciplinary activities involving Environmental Education and Physical Education in non-formal Amazonian spaces. 45 high school students from two schools in the city of Manaus participated, one state public and the other federal, with all participants in the project entitled "Environmental Education: awareness through physical activity practices" at IFAM - Campus Manaus Centro. The action research was divided into three stages: 1) a) selection of research participants and collection of information about the places where the research was carried out; b) diagnostic application to collect the students' initial knowledge through the questionnaire in a formal space; c) expository dialogue, planned based on the initial knowledge verified through the diagnostic questionnaire; d) visit in a non-formal Amazonian Soka Amazon space, and e) the environmental projects workshop to verify the students' final learning. 2) a) Analysis of the data collected: field diary, questionnaires, drawings, projects elaborated in the workshop; were explored by means of analysis criteria (categorical analysis) and by rubrics, in the sequence, we treat the results obtained that allowed the creation of tables, charts, graphs. 3) a) Elaboration of the educational product: a didactic guide accompanied by a video highlighting the reserve environments where teaching activities can be developed in the context of the Amazon, serving as a subsidy for students and teachers. The non-formal spaces used in the perspective of teaching expand the regional Amazonian knowledge offered by direct contact with these ecosystems and physical activities when carried out in natural environments, arouse benefits in the physiological, cognitive, learning and integral training of students.